A data processing system for hospital bacteriology. Issue 1 (February 1970) - Alexander, M. K.; Connigale, J.; Johnson, T.; Poulter, I. R.; Wakefield, J.
Abstract : A system for the automatic capture and retrieval of information contained in routine bacteriology reports is described. The system depends on the preparation of reports on an electric typewriter producing punched paper tape as a byproduct. Periodically the information contained on the tape is analysed by computer. The potential value of the system for the analysis of the results of antibiotic sensitivity testing and for the study of the epidemiology of hospital infections is briefly discussed.